The excitatory effect of hydrogen sulfide on rat colonic muscle contraction and the underlying mechanism - Xiaojing Quan; Wei Chen; Bin Qin; Jinhai Wang; Hesheng Luo; Fei Dai (Elsevier, 2022)
H2S is a well-known relaxant regulator in muscle contraction but little attention has been paid to its excitatory effect on colonic motility. To investigate the excitation of H2S on rat colonic contraction and the underlying mechanism, the muscle contractile activity was assessed by an organ bath system, the level of substance P (SP) in the colon was detected using enzyme immunoassay kits, L-type Ca2+ channel currents (ICa,L) and large conductance Ca2+-activated K+ channel currents (IBK) in smooth muscle cells (SMCs) were measured by patch-clamp electrophysiology. The results show that the H2S donor NaHS (100 μM) reversed the relaxation of the NO donor SNP on colonic muscle contraction. Pretreatment with the TRPV1 antagonist and the neurokinin receptor antagonists attenuated the NaHS-induced excitation. Incubation of colon with NaHS increased the SP level. In freshly isolated SMCs, NaHS exerted a biphasic effect on ICa,L and concentration-dependently inhibited the IBK. And 100 μM NaHS partially reversed the SNP-induced changes in ICa,L and IBK. We concluded that exogenous H2S exerts a potential excitatory effect on colonic motility, which may be achieved by activating SP release from afferent nerves in combination with a direct activation of ICa,L and suppression of IBK in SMCs.